ANALISIS HIERARKI HUKUM PEMBERIAN TUNJANGAN JABATAN FUNGSIONAL ANALIS KEUANGAN PUSAT DAN DAERAH PASCA DIBERLAKUKANNYA PERATURAN MENTERI PEMBERDAYAAN APARATUR NEGARA DAN REFORMASI BIROKRASI REPUBLIK INDONESIA NOMOR 17 TAHUN 2021 ( STUDI KASUS DI PEMERINTAH - Dewantara, Andrian; Karyoto, Karyoto (Universitas Islam Kadiri, 2023)
The legal hierarchy for granting functional position allowances for Intergovernmental Fiscal Analyst after the enactment of the Minister of Administrative and Bureaucratic Reform of the Republic of Indonesia Number 17 of 2021, namely according to Act No. 12 of 2011 and as changed Act No. 13 of 2022 concerning Formation of Legislation, which contains the types and order of laws and regulations. Implementation of Functional Allowances After the Enactment of the Minister of Administrative and Bureaucratic Reform of the Republic of Indonesia Number 17 of 2021, namely by implementing bureaucratic simplification in the Kediri City area on December 31, 2021 by Decree of the Mayor of Kediri Number 821.2/2146/419.203/2021 concerning Equalization of Administrative Positions to In Functional Positions in the Kediri City Government Environment, it is in accordance with the Bureaucratic Reform. However, regarding the amount of Functional Position Allowance, the Kediri City Government uses the basis of the Circular of the Director General of Treasury of the Ministry of Finance of the Republic of Indonesia Number SE-21/PB/2007 concerning Structural Position Allowance to determine the amount of Functional Position Allowance, which is stated in the Statement of Occupying Position. In the science of legislation, there is a theory of hierarchy. The Hierarchy Theory is a theory which states that the legal system is arranged in stages and levels like a ladder. The author uses the type of Socio Research/Empirical research. The research approach used is the approach of legal sociology, legal anthropology or legal psychology. Research data or legal materials used are research data in the form of primary data, secondary data, and tertiary data. Techniques for Collection and Management of Legal Materials, in which the author adds components such as location and time of research, informants, and respondents. Discussion and Research Analysis that is using deductive analysis in writing. So based on the discussion above, it can be concluded that the Equalization of Administrative Positions into Functional Positions within the Kediri City Government is in accordance with the Bureaucratic Reform. However, regarding the amount of Functional Position Allowance after the entry into force of the Bureaucratic Reform is not in accordance with the law . Then on April 4, 2022 the Presidential Regulation of the Republic of Indonesia Number 50 of 2022 was issued concerning Income of Administrative Officials Affected by Bureaucratic Arrangements, until the research was carried out there was no decision on adjusting the amount of Functional Position Allowances in the City Government of Kediri in accordance with Regulations.